Diseño de cargos por competencias para la empresa Selecta. - Lasso Boada, Verónica Elizabeth (2011)
This paper "Designing Charges Competencies for SALCTA company" has tried to develop a product objectively for this company, which reflects current responsibilities, essential activities, requirements, knowledge, skills and abilities necessary to perform each position.